On a Nonhomogeneous Timoshenko System with Nonlocal Constraints - Said Mesloub; Faten Aldosari (Journal of Function Spaces)
Our main concern in this paper is to prove the well posedness of a nonhomogeneous Timoshenko system with two damping terms. The system is supplemented by some initial and nonlocal boundary conditions of integral type. The uniqueness and continuous dependence of the solution on the given data follow from some established a priori bounds, and the proof of the existence of the solution is based on some density arguments.